Experimental investigation on the performance of direct-expansion roof-PV/T heat pump system. (15th March 2020) - Shao, Nina; Ma, Liangdong; Zhang, Jili
Abstract: Although the integration of photovoltaic-thermal (PV/T) heat pump systems on buildings can assist in reducing the electricity demand of high-energy consuming buildings, the large occupation area of PV/T modules hinders its popularization. To overcome this problem, a novel PV/T evaporation roof coupled with a heat pump system composed of electronic expansion valves, a condenser and a compressor is proposed, which serves as an electric generator, evaporator for the heat pump system and the external surface of a building roof. This paper investigates the actual operating performance of the direct-expansion roof-PV/T heat pump system under different seasonal conditions. The structure and design of PV/T evaporation roof and the whole system are first presented, followed by the construction of an experimental platform and finally the operation of the system is analyzed through performance evaluation indices and field-testing. The experimental results indicated that the system performed better in the summer than in the winter, with the electrical efficiency, thermal efficiency and overall efficiency averaging at 11.23%, 64.25% and 83.32%, respectively. The average COP was 5.9, with a maximum value of 8.9. Additionally, it took 2 h to heat the water within a 1.5 m 3 heat storage tank from 25 °C to 60 °C, which was twice as fast as under winter conditions. Meanwhile, a significant decrease in system performance resulting from changes in environmental parameters in the winter was observed. The average electrical efficiency, thermal efficiency, and overall efficiency were 11.67%, 60.17% and 78.84%, respectively, while the average and maximum COP were 3.7 and 5.24 respectively. Highlights: A novel direct-expansion roof-PV/T heat pump system is experimentally investigated. The performance evaluation index of PV/T heat pump system is analyzed. The system performance and operating parameters in summer and winter are contrasted.